The influence of non-verbal body language on sport performance in professional tennis - Martinez-Gallego, R.; Carrillo Molina, D. (Coaching and Sport Science Review, 2019)
The main objective of this study was to analyse the relationship between players´ non-verbal body language and their performance in sport. The sample consists of a total of 477 actions from 40 players competing in the ATP Tour. All actions were taken from tiebreaks in official tournaments. The categories that were analyzed were previous performance, dominant non-verbal body language, submissive non-verbal body language, and performance later on. Results show how the players´ non verbal body language impacts on their performance later on. Thus, we can conclude that following dominant non-verbal body language, the probabilities of better performance in the next point are greater than following submissive non-verbal body language. Therefore, it is important to train these aspects as an extra tool to improve players´ performance.